2013
DOI: 10.1371/journal.pone.0075483
|View full text |Cite|
|
Sign up to set email alerts
|

The Tumor Suppressor Gene, RASSF1A, Is Essential for Protection against Inflammation -Induced Injury

Abstract: Ras association domain family protein 1A (RASSF1A) is a tumor suppressor gene silenced in cancer. Here we report that RASSF1A is a novel regulator of intestinal inflammation as Rassf1a+/−, Rassf1a−/− and an intestinal epithelial cell specific knockout mouse (Rassf1a IEC-KO) rapidly became sick following dextran sulphate sodium (DSS) administration, a chemical inducer of colitis. Rassf1a knockout mice displayed clinical symptoms of inflammatory bowel disease including: increased intestinal permeability, enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 74 publications
(102 reference statements)
1
58
0
Order By: Relevance
“…Imaginably, the cancer cells can secrete the intracellular netrin-1 and activate the receptors on the plasma membrane via autocrine, leading to YAP signaling regulation. It is also reported that YAP activity in modulation of proliferation and senescence is regulated by Ras association domain family 1A (RASSF1A) (28) and RASSF4 (29), respectively. The RASSF family of proteins consists of 10 members, most of which are considered as tumor suppressor proteins that undergo loss of expression through promoter methylation in various types of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Imaginably, the cancer cells can secrete the intracellular netrin-1 and activate the receptors on the plasma membrane via autocrine, leading to YAP signaling regulation. It is also reported that YAP activity in modulation of proliferation and senescence is regulated by Ras association domain family 1A (RASSF1A) (28) and RASSF4 (29), respectively. The RASSF family of proteins consists of 10 members, most of which are considered as tumor suppressor proteins that undergo loss of expression through promoter methylation in various types of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…We also recently demonstrated that, under conditions of acute intestinal inflammation, RASSF1A restricts NFjB activity by interfering with the ability of the membrane proximal TLR/MyD88/TRAF6/IRAK2/4 complex to promote downstream signaling to NFjB [46]. The restriction of NFjB activity also led to restriction of tyrosine (Y) 357 phosphorylation of Yes associated protein (YAP), a key Hippo-dependent transcription factor linked to proliferation [46]. We determined that Y357 phosphorylation of YAP may arise due to increased inflammation and DNA damage -both of which are prominent during intestinal inflammation injury stimulated by the colonic irritant, dextran sodium sulfate (DSS) [46].…”
Section: Kdamentioning
confidence: 97%
“…These associations function to prevent excessive growth and allow RASSF1A to function as a tumor suppressor. We also recently demonstrated that, under conditions of acute intestinal inflammation, RASSF1A restricts NFjB activity by interfering with the ability of the membrane proximal TLR/MyD88/TRAF6/IRAK2/4 complex to promote downstream signaling to NFjB [46]. The restriction of NFjB activity also led to restriction of tyrosine (Y) 357 phosphorylation of Yes associated protein (YAP), a key Hippo-dependent transcription factor linked to proliferation [46].…”
Section: Kdamentioning
confidence: 99%
See 2 more Smart Citations